Studi fenomenologis modal sosial warga masyarakat nelayan di daerah pesisir - M Hizbullah AshShidqi; Devi Puspitasari (INNER: Journal of Psychological Research, 2023)
Mengare Island is an area surrounded by abundant mangrove vegetation, making it a tourist attraction. This island is located in the southwest of Bungah sub-district, Gresik district. Mengare Island has tens of hectares of salt fish ponds with its own characteristic, namely milkfish. The area has problems regarding human resource issues, one of which is an unstable economy due to a lack of catches. The purpose of this study is to provide an overview of Social Capital in Fisherman Communities in Coastal Areas. The subjects of this study were fishermen on the coast of the island of Mengare. The method used is qualitative with observation and interview data collection techniques. The data analysis technique used is descriptive phenomenology (DPA). The results of the study show that the social capital of fishermen in coastal areas is cooperation, solidarity, and also dependence on one another. Keywords: Social capital, Fishermen, Coastal